PENGARUH KOMPETENSI MANAJERIAL KEPALA SEKOLAH DAN SUPERVISI AKADEMIK TERHADAP KINERJA GURU - Meidiana, Meidiana; Ahmad, Syarwani; Destiniar, Destiniar (Graduate Program Magister Manajemen Pendidikan, 2020)
This study aimed at determining the significant effect of principals' managerial competence and academic supervision on teacher performance. This study aims to determine the effect of principals 'managerial competence on teacher performance, the effect of academic supervision on teacher performance and the influence of principals' managerial competence and academic supervision together on teacher performance. This research was conducted at SMA Negeri 3 Martapura. In this study using quantitative descriptive method. The research method used is the test method of correlation, partial and simultaneous using the SPSS 16.0 program. The results of this study indicate, 1) there is a significant influence of managerial competence of principals on teacher performance; 2) there is a significant influence of academic supervision on teacher performance; 3) there is a significant influence on the principal's managerial competence and academic supervision on teacher performance. The conclusion is that there is a significant influence on the principal's managerial competence and academic supervision on the performance of teachers at SMA Negeri 3 Martapura.